Assessment of Ogan River Water Quality Kabupaten OKU South Sumatera by NSFWQI Method - Eriyana Yulistia; Fauziyah Fauziyah; Hermansyah Hermansyah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
A Study of physicochemical and microbiology analysis in Ogan River Kabupaten Ogan Komering Ulu was carried out in Mei-Juny 2016. The purpose of this study was to determine the water quality status of Ogan River by using National Sanition Foundation Water Quality Index. Water quality status was studied at six selected stations to represent different localities with varying anthropogenic discharge. Water samples were taken by purposive sampling method. Physicochemical and microbiology parameters of samples were measured pH, temperature, Turbidity, Total Suspended Solids, Dissolved Oxygent, Biochemical Oxygent Demand, Nitrat, Phospate, and Fecal Coliform following standard method. The river water quality status is medium, the value ranged 56-57. Based on these indices it is concluded that the anthropogenic activies along Ogan River effected quality of water Ogan River.